Designing a unified damping and cross-coupling rejection controller for LCL filtered PV-based islanded microgrids - Dristi Datta; Subrata K. Sarker; Md. Rafiqul Islam Sheikh (Engineering Science and Technology, an International Journal, 2022)
To meet up with the increasing power demands globally, renewables have come into focus recently. Due to the unpredictable nature of the energy in Microgrids (MGs), it generates oscillation or harmonics into the power. Smooth power performance can be obtained by LCL filter, however, that produces undamped resonance frequency that significantly decreases the system performance. This paper presents an improved design of a multi-input multi-output (MIMO) Integral-Linear-Quadratic-Gaussian (ILQG) control approach for LCL filtered photovoltaic (PV) based islanded microgrid (MG) system. In this study, we have proposed a unified controller that can reject the oscillation and cross-coupling effect from the system. The architecture of the proposed controller is based on the artificial neural network (ANN) based maximum power point tracking (MPPT) algorithm. The performance of the controller is verified by time- and frequency domain response and proves better performance in terms of bandwidth, damping, tracking, and reduction of cross-coupling effects for LCL filtered PV-based islanded MGs. Additionally, the robustness of the controller is also analyzed by shifting the resonance frequency of the LCL filter by varying the inductor and capacitor. Different types of load structures are also considered for the performance analysis of the proposed unified controller. Additionally, a comparative analysis in terms of bandwidth and qualitative content is further studied here to explicit the high effectiveness of the proposed unified controller. Simulation results of open- and closed-loop systems also prove the high effectiveness of the controller under different load conditions.